HAMBATAN ORANGTUA TERHADAP PEMBELAJARAN DARING PADA ANAK DI MASA PANDEMI - Hasanah Hasanah; Rini Susiani; Maulida Maulida; Irma Aryani; Syarifah Rahmiza Muzana; Suryani Suryani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Parents plays an important role in their children’s learning and development, furthermore parentsare children’s first educators, children are watching their parents and learning happens in everyday moment parents share with their children. A phenomenon that covid-19 pandemic has a major impact toward the education sector, the government has implemented a learning policy, namely learning from home. This study aims to find out what obstacles are experienced by parents while accompanying children to learn at home during covid 19 pandemic. This study employed a qualitative descriptive research method with case study approach. The sample are nine parents whose children attended elementary school. The result of this study indicates that in general the obstacles of parent in assisting children learning from home are: First, inability to teach and explain the material properly by parents. Second, the difficulty of parent to create children enthusiastic to participate in online learning. Third, Lack of time to accompany children because they have to work and parents are impatient in accompanying children when studying at home. Fourth, parent not accustomed to using technology such as difficulties in operating gadget and computer.This research is expected to be able to explore the obstacles of parent in assisting children when learning at home so that this research is able to contribute to further researcher in exploring the solutions to these problems.